أثار القراءة في كتابة الإنشاء بكليّة المعلّمات الإسلامية - Ruhamauliyah Meiliyati; Wahyu Hanafi Putra (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2021)
In Arabic learning, there are four skills, namely listening, speaking, reading and writing. These four skills are interrelated. writing is one of the difficult skill because it is an activity to express ideas in the mind to littering. The broader of knowledge and vocabularies of an author will produce good literature. And the means to get knowledge by reading. Because reading is an activity to usderstand the purpose and increasing knowledge from a literature. This study to know the influence of reading habits on writing skills of 4th grade at Arrisalah Islamic International College on academic year 2019-2020. The researcher used descriptive quantitative as a method of study. The data were collected using questionnaire and test . The result of this study revealed reading is not only factor influencing students’ writing skills. The study environment and facilities contributed to support writing skills and give students more space to get vocabularies in the college environment.